Intertemporal consumption and debt aversion: An experimental study - Thomas Meissner (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2013)
This paper tests how subjects behave in an intertemporal consumption/saving experiment when borrowing is allowed and whether subjects treat debt differently than savings. Two treatments create environments where either saving or borrowing is required for optimal consumption. Since both treatments share the same optimal consumption levels, actual consumption choices can be directly compared across treatments. The experimental findings imply that deviations from optimal behavior are higher when subjects have to borrow than when they have to save in order to consume optimally, suggesting debt-aversion. Signifiant underconsumption is observed when subjects have to borrow in order to reach optimal consumption. Only weak evidence is found suggesting that subjects over-consume when saving is necessary for optimal consumption.
Keywords: C91; D81; E21; 330; Laboratory Experiment; Intertemporal Consumption; Consumption Smoothing; Debt Aversion